Pakistan: Impacts of the Ukraine and global crises on the economy and poverty - Qureshi, Tehseen Ahmed; Rana, Abdul Wajid (International Food Policy Research Institute, 2022)
Russia-Ukraine conflict is increasing uncertainty, which in turn is fueling volatility in global commodity and financial markets. Global food, fuel, and fertilizer prices have risen sharply driven largely by this conflict and sanctions imposed on Russia. Export bans and disruptions in global trade and international supply chains have also contributed to rising prices having implications for economic and food security for countries like Pakistan. This price shock came at a time when the fragile economy of the country was recovering from the effects of COVID-19 pandemic and grappling with the threat of climate change (severe heat wave in March-April 2022 and cataclysmic floods in August-September 2022) Price shock has affected the Current Account Deficit (CAD) and Balance of Payments since Pakistan is a net importer of oil, LNG, edible oil, and now wheat and may impact economic growth in FY2023. In March 2022, per barrel price of oil saw an increase of 59 percent (USD118) as compared to December 2021. It is estimated that ‘as long as the conflict in Ukraine rages on, oil prices will remain above USD100/barrel, even though they are closer to USD90/barrel in October 2022. In 2022, gas prices are expected to increase by at least 50 percent, especially in Europe, where they have increased by more than 2.5 times in the last year due to its heavy dependency on Russian energy’.2 Palm oil and wheat prices increased by 56 and 100 percent in real terms, respectively, between June 2021 and April 2022. The CAD increased from USD 3.1 billion in FY2021 to 17.7 billion in FY2022. However, excluding the impact of oil and edible oil, the CAD could have fallen to around USD 7.7 billion. The increase in administered prices of fuel and electricity as well as shortages in wheat production has increased food inflation from 16.6 percent in September 2021 to 28.6 percent in September 2022 (YoY) while the overall CPI increased from 9.0 to 23.2 percent during the same period. Pakistan’s trade volume with Ukraine and Russia has been rising. During the last 24 years, the bilateral trade between Pakistan and Ukraine was USD 800 million including USD 739 million imports in 2021 (1.3 percent of Pakistan’s total imports). Likewise, the trade with Russia was USD 711 million including USD 537 million imports in 2021 (1.3 percent of Pakistan’s total imports).